The persuasion as an instrument of political action in 5th century B.C. Athens: the case of Pericles - Neves dos Santos, Ricardo (Romanitas - Revista de Estudos Grecolatinos, 2021)
In the book History of the Peloponnesian War, Thucydides states that Pericles, the eminent Athenian politician, “could contain the crowd without threatening its freedom, and lead it instead of being led by it, as he did not resort to adulation to obtain strength by less worthy means” (Thuc., 2, 65, 8). If Pericles did not use imposition or adulation to govern his fellow citizens, what then was his main instrument of political action? In this article, we will defend the proposition that persuasion was the supreme instrument used by Pericles in conducting his policy among the Athenians. During the analysis of excerpts from Pericles’ third speech reported by Thucydides (Thuc., 2, 60-4), four central aspects of how this was configured will be presented.